MODIFIED INVERTED KUMARASWAMY DISTRIBUTION USING INVERSE POWER FUNCTION: PROPERTIES AND APPLICATIONS - Yusuf, Hauwau; Usman, Abubakar; Yahaya, Abukakar; Sadiq, Ibrahim Abubakar; Bello, Olalekan Akanji; Adamu, Saudat Aliyu (FUDMA JOURNAL OF SCIENCES, 2025)
In the area of distribution theory, statisticians have proposed and developed new models for generalizing the existing ones to make them more flexible and to aid their application in a variety of fields. In this article, we present a new distribution called the Modified Inverted Kumaraswamy Distribution Using Inverse Power Function with three positive parameters, which extends the Inverted Kumaraswamy distribution with two parameters. Some statistical properties of the MIK distribution, such as explicit expressions for the quantile function, probability-weighted moments, moments, generating function, Reliability function, hazard function, and order statistics are discussed. A maximum likelihood estimation technique is employed to estimate the model parameters and the simulation study is presented. The superiority of the new distribution is illustrated with an application to a real data set. The results showed that the new distribution fits better in the real data set amongst the range of distributions considered.